A Study to Assess the Effectiveness of Midwife-Led Psychoeducation on Childbirth Fear and Childbirth Efficiency in Primigravida Mothers of Selected Hospital of Navi Mumbai - Maria Thomas, Ann; Solomon, Smriti G. (Indian Journal of Nursing Sciences, 2024)
Aim: This study examines the effects of midwife-led psychoeducation on delivery fear and efficiency in primigravida moms in Navi Mumbai hospitals. Method: The researcher used quantitative evaluator research. Aquasi-experimental research approach was chosen for the investigation. Sample size for the study is 300. For this study, simple random sampling was performed. Results were presented using descriptive and inferential statistics. Demographic data, childbirth fear categorization, and efficacy were presented as frequency and percentage. T-test was used to compare pre- and post-test delivery fear and efficacy levels. Childbirth fear and efficacy were correlated with demographic characteristics using Chi-square testing. Result: Pre-intervention primigravida mothers’ delivery fear scores in the experimental and control groups. The experimental group contained 89 (59%) respondents with severe fear and 10 (7%) with low fear. 79 (53%) of the control group indicated high dread, whereas 8 (5% expressed low fear. Pre-interventional delivery efficacy scores for experimental and control primigravida moms. In the experimental group, 78 (52%) had average birthing efficacy, 63 (42%) with poor, and 9 (6% with good). Most of 72 (48%) control group members had low birth effectiveness scores, followed by 60 (40%) average and 18 (12%) good. Conclusion: This study shows that midwife-led psychoeducation reduces primigravida moms’ delivery fear and efficacy. Primigravida mothers’ labor efficacy and fear scores improve.